Professoras dos anos iniciais do ensino fundamental da rede municipal de São Paulo: o que dizem a respeito do ensino de geografia e do ciclo de alfabetização - Solano, Fernando Bianco [UNIFESP] (2019)
The work with the Humanities in the Literacy Cycle of Elementary School has long been a matter of debate in the corridors of school units, considering the possible focus given to the curricular components that deal with the issues of teaching to read and to count. In this sense, the present work aims to identify what the teachers of the Cycle of Literacy of the Municipal Network of São Paulo say about the teaching of the Human Sciences and of the continuous formation. In the course of the research, we embark on the issues of public literacy policies in a historical and contemporary perspective, presenting their nuances in the midst of a city permeated by inequalities, bringing the discussions about the Geography component closer to the specificities of the Literacy Cycle. On the way we approach the public school and the policies of in-service and out-of-service training, respectively the Special Integral Training Day (JEIF) and the National Pact for Literacy in the Right Age (PNAIC). Listening to the teachers, based on a semi-structured interview, was fundamental to make some considerations about the teachers' perception of continuing education; the importance attributed to the Human Sciences and the component of Geography; the relationships established between the alphabetical writing system and the geographical lettering, among other points. In this way we understand that the research presents elements that can contribute to the debate about the Literacy Cycle, the continuing education and the teaching of the Human Sciences.